From value chains to food webs: The quest for lasting food systems. (April 2021) - Knorr, D.; Augustin, M.A.
Abstract: Background: The concepts of sustainability and food systems have developed over time and their definitions vary depending on different discipline perspectives. There has been an evolution of the term sustainability, particularly as it relates to the sustainability of food systems. However, most discussions around food systems sustainability focus on food production and nutrition, and omit considerations of major parts of the food value chain, notably food processing and preparation. Scope and approach: In this review, the transitions required to move from linear food chains to closed loop systems to the wider food web for more sustainable food systems are discussed. The interdependencies between resource use, the activities in the food chain and various sustainability indicators are considered. A model for stimulating discussion about the complexity of value chains in the food web is presented. Key findings and conclusions: There is an urgent need for radical change in the food system to ensure the long term sustainability of the planet. Clear, understandable and globally accepted definitions and indicators for sustainability need to be developed. The increasing complexities in food value chains have to be considered when developing solutions for enhancing food systems sustainability. Food processing and preparation have crucial roles in transforming existing food systems to make them more sustainable. A systems-based approach to developing sustainable food systems, that includes improving natural resource use, reducing environmental impact, examining new food resources, enhancing consumer trust and understanding, and developing profitable market opportunity-led solutions for food and nutrition security, is required. Highlights: Globally accepted definitions and indicators for sustainability are essential. Food processing and preparation have crucial roles in food systems sustainability. Transitioning from linear to closed looped food chains improves food sustainability. Resource use, food chain activities and sustainability indicators are interlinked. There is an urgency for radical change in the food system for sustainable futures.